Zwischen dem Gedenken und der Ideologisierung der Kämpfe der Legionen in den Ostkarpaten in der polnischen Literatur der Zwischenkriegszeit - Jagoda Wierzejska (Góry, Literatura, Kultura)
The article provides a critical analysis of representations of the Eastern Carpathians present in the interwar Polish literature, as a space marked by memory of the legionary battles during the Great War.